-x+12=2x-6

Simple and best practice solution for -x+12=2x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+12=2x-6 equation:


Simplifying
-1x + 12 = 2x + -6

Reorder the terms:
12 + -1x = 2x + -6

Reorder the terms:
12 + -1x = -6 + 2x

Solving
12 + -1x = -6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + -1x + -2x = -6 + 2x + -2x

Combine like terms: -1x + -2x = -3x
12 + -3x = -6 + 2x + -2x

Combine like terms: 2x + -2x = 0
12 + -3x = -6 + 0
12 + -3x = -6

Add '-12' to each side of the equation.
12 + -12 + -3x = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -3x = -6 + -12
-3x = -6 + -12

Combine like terms: -6 + -12 = -18
-3x = -18

Divide each side by '-3'.
x = 6

Simplifying
x = 6

See similar equations:

| -x+7=7x-9 | | 8+2x=12x-12 | | 8.4n+6-2n=2(n+3) | | -5(b+4)+3b=-2(1+5b)+6 | | 4x-7(3x+3)=183 | | A=h/2(b+c) | | t^2+4t+9=0 | | 14+q=35 | | 528-20=x | | 5-v=9 | | 4-1/2x=6 | | 27+3x-2x^2=0 | | 3x+28=7x+7+3x | | 14x+5x-3=-60 | | 8=0.285x+-0.06444 | | -0.1w-1.1=0.3w+2.9 | | K+15=2 | | 2x-2y-5x+4+8y= | | 5(3x+6)=15(x+2) | | -4b-2=13+2b | | 15=3(k+6) | | 4h-3h=13 | | Movern=p-6 | | -1/2x-3=4 | | -6=4-1/2x | | 5(x-7)+2=4(x+3) | | 3x+2=x+4x+2 | | 4-(5-6x)=2x-3 | | x*2-40=900 | | C=-5c+1 | | -1+3(8z-1)=-(-6z-3)+5 | | 12m+5=104 |

Equations solver categories